2020
DOI: 10.1111/jcal.12431
|View full text |Cite
|
Sign up to set email alerts
|

How students emerge as learning leaders in small group online discussions

Abstract: In this study, we examined the role of leadership styles and multi‐dimensional learner engagement in how students emerge as learning leaders in asynchronous online discussions. Grounded in the conceptual framework of two dominant leadership styles of transformational and transactional leadership, this study applies the two leadership styles—transformational leadership and transactional leadership—to the Leader Identification Method (LIM) which defines three types of leader roles (i.e., full, transactional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…Lastly, replying behavior proved to be the only leader behavior that predicted member participation. According to Kim et al [ 7 ], replying with individualized messages is considered a person-focused leadership behavior, which induces positive emotions among group members, and more frequent member presence and engagement in online collaboration as a result.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, replying behavior proved to be the only leader behavior that predicted member participation. According to Kim et al [ 7 ], replying with individualized messages is considered a person-focused leadership behavior, which induces positive emotions among group members, and more frequent member presence and engagement in online collaboration as a result.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…There are two preconditions for its occurrence: 1) the absence of an assigned leader or the negligence of the assigned leader, and 2) the presence of group members with strong working and organizational capabilities [ 13 , 26 ]. It is found that members with high intelligence, active participation, and positive self-views are more likely to emerge as leaders [ 7 , 13 , 27 ].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…L2 acquisition is necessarily a social not individual activity and therefore occurs through interactions with others (Lantolf, 2000). it course performance (Kim, Lee, & Wang, 2020). Such student-student interactions can be particularly beneficial to students of a more reserved disposition (Coffey, 2012).…”
Section: Introductionmentioning
confidence: 99%